Polyoxometalates as nanoscale building blocks for the formation of functional materials - Zhang, Li Zhi (2009)
Polyoxometalates (POMs) are nano-sized metal-oxygen cluster species with a diverse compositional range and an enormous structural variety. They are powerful building blocks in the field of materials because of the following: (1) POMs can easily dissolve in water or organic solvent and hold the same polyoxoanion structure as that in the solid state; (2) POMs possess various charge, shape and bulk; (3) POMs can accept various numbers of electrons; (4) POMs are good ligands with multifunctional coordination sites.